Critical Media Analysis Using Ai-powered Chatbots: Considerations And Applications In Efl Classrooms - Ali Belabbes; Fatiha Hamitouche (The Journal of Studies in Language, Culture and Society)
Despite the growing body of research on the use of applications of artificial intelligence in teaching and learning, little is known about the impact of classroom teaching strategies on empowering students' as questioners and highly skilled at using AI-powered chatbots. The purpose of the present study was to examine the influence of a direct instruction program of strategies for analysis of argumentation on students' quality of questions asked to AI tools for answers supporting their critically evaluation of media messages. Within this framework, this study examined the effect of explicit teaching about arguments on EFL students’ strategic questions asked to AI-powered chatbots (ChatGPT & Gemini(formerly Google Bard)) for getting answers supporting analysis of textual content of media texts with the intent to identify bias and clarify ideological perspectives the texts display. This was a one-semester longitudinal study with 88 university students studying in the Department of English at the University of Mascara in Algeria. Conducting pre- and post-tests, the researchers demonstrated a significant positive correlation between a critical thinking course and students' development of ability to construct good questions for answers generated by AI chabots (GPT and Gemini) to infer information for responding critically to media messages. The obtained results revealed that the intervention was effective and the ability of students to ask meaningful questions was increased to a noticeable extent. The researchers concluded the paper with implications for EFL instructions to employ different pedagogical interventions for supporting effective use of AI class.